Elucidation of the potential antioxidant compound and mechanism of mung bean using network pharmacology and in vitro anti-oxidative activity - Kong, Feng; Li, Yue; Zhang, Yuping; Zeng, Qinghua; Guo, Xingfeng (Frontiers in Sustainable Food Systems, 2022)
Mung bean is rich in bioactive components, but the main compound and pharmacological mechanism in reducing oxidative and free radical damage are unclear. Network pharmacology and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) radical scavenging activities were employed to uncover the antioxidant mechanism of potentially active compounds, considering the interactions between mung bean targets and oxidative and free radical damage. These key targets were analyzed by protein–protein interactions (PPIs), and key genes were used to find the biological pathway and therapeutic mechanism by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The results showed that five antioxidant components and 18 mung bean targets were screened. β-carotene and vitexin both played a crucial role in mung bean against oxidative and free radical damage, and the ABTS radical scavenging activities of β-carotene and vitexin were 94.84 and 87.79%, which were equivalent to those of vitamin C. Key targets may be AR, HSP90AA1, MYC, and CASP3 for mung bean to exert antioxidant activity. GO and KEGG indicated that mung bean may mainly act on thyroid hormone signaling pathway, estrogen signaling pathway, p53 signaling pathway, etc. In vitro antioxidant activity tests showed that the bioactive ingredients of mung beans had great antioxidant activity. Network pharmacology analysis also revealed the underlying molecular mechanisms of oxidative and free radical damage. This study provides new insights and evidence to explore the bioactive compounds and biological functions of food cereals and legumes, as well as a reference for the functional evaluation of food ingredients and the development of functional foods.